2019
DOI: 10.1017/s1744552319000041
|View full text |Cite
|
Sign up to set email alerts
|

On the edges of the law: sex workers’ legal consciousness in England

Abstract: In England, sex workers are placed at the edges of the law. How the social and legal status of sex workers impacts on their perception of and interaction with the law in a semi-legal setting has not yet been explored. Drawing on fifty-two qualitative interviews with indoor and outdoor sex workers in England, this study investigates their disposition to the law, legality and the state. The commonalities and discrepancies between the experiences of indoor and outdoor sex workers reveal the influence of the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Groups’ understanding and perception of the law fundamentally shape their engagement with it. 53 Our findings suggest that the coaches in general were somewhat engaged with the law (See Table 2). Neither group of coaches perceived concussion guidance or laws as a “game to play.” This differs from Sarat’s finding that an individual’s engagement included hoping the law’s power and authority could be made to work for them.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Groups’ understanding and perception of the law fundamentally shape their engagement with it. 53 Our findings suggest that the coaches in general were somewhat engaged with the law (See Table 2). Neither group of coaches perceived concussion guidance or laws as a “game to play.” This differs from Sarat’s finding that an individual’s engagement included hoping the law’s power and authority could be made to work for them.…”
Section: Discussionmentioning
confidence: 69%
“…A female Scottish coach noted, “the biggest problem … is the majority of [medical] research … is around males” and asked, “physiologically what are the differences?” She perceived the guidelines as arbitrary and overly prescriptive. “Everyone heals at difference rates … it is just a grey area … you are fine or you’re not [only] because the guidance says that you are.” This lack of resistance differs from much of the legal consciousness research, which has found active resistance in the “welfare poor,” 54 mixed status immigrant families, 56 formerly incarcerated job seekers, 25 sex workers in England, 53 labor organizers, 24 and during police-citizen encounters. 47…”
Section: Discussionmentioning
confidence: 69%
“…For any hate crime policy to work, it would require police officers (and others working in the criminal justice system) to put their assumptions about sex workers to one side and recognise agency in their involvement with the industry, their boundaries and ability to engage in and withdraw consent. Research has found that even those sex workers who had positive experiences with the police did not expect respectful treatment (Klambauer, 2018) and there is vast evidence that the police perpetuate violence and stigma, codify gender norms, and stereotype sex workers based off media representations (Klambauer, 2019;Bowen et al, 2021;ICRSE, 2020).…”
Section: Peer-reviewed Articlementioning
confidence: 99%
“…The stigma that sex workers face cannot be extricated from broader social structures within which the police not only exist but are also charged with exercising state-sanctioned power (Klambauer, 2017). While the public in England and Wales look to the police to protect and serve, by preventing crime, improving community safety and responding to incidents in a competent and compassionate manner (BMG, 2019), sex workers rarely receive the same treatment (Klambauer, 2017(Klambauer, , 2019. For sex workers, the police are not always a source of protection.…”
Section: The Socio-legal Contextmentioning
confidence: 99%
“…In sex work, the intersections of power and legitimacy, the politics of respectability, stigma and social exclusion are made clear: the type of work a person engages in and how they undertake it, their gender, race and ethnicity, migration status and their physical abilities — to name but a few — are all embedded in the concept of the ‘Whorearchy’, which combines levels of client contact, police engagement and wider social structures to stratify the sex industry (Bosch, 2016 ; Bowen, 2021 ; Sciortino, 2016 ). Street-based sex workers in particular, a group often comprising individuals with the least social power, report high levels of social stigma and poor experiences with the police (Klambauer, 2019 ). The stigma that sex workers face cannot be extricated from broader social structures within which the police not only exist but are also charged with exercising state-sanctioned power (Klambauer, 2017 ).…”
Section: Introductionmentioning
confidence: 99%